PENGARUH AROMATHERAPI LEMON TERHADAP PENURUNAN NYERI DISMINORE PADA REMAJA PUTRI KELAS 8 DI MTS MATHLA’UL ANWAR RUMPIN BOGOR TAHUN 2023 - Ramdani, Ruden Lahilia; Gapmelezy, Ezzy (Jurnal Ilmiah Global Education, 2023)
Dysmenorrhea is a complaint that is often experienced by women during menstruation. Dysmenorrhea can be treated with non-pharmacology, one of which is with lemon aromatherapy which contains limonene and can inhibit prostagladin so as to reduce pain during menstruation. The purpose of this study was to determine the Effect of Lemon Aromatherapy on Reducing Dysmenorrhea Pain in Grade 8 Young Women at Mts Mathla'ul Anwar. This research design is a Quantitative research with a Quasi-Experimental Approach with One Prestes-Posttest-Design design. Measuring using the Numeric Rating Scale (NRS), the number of samples was 23 Grade 8 girls at Mts Mathla'ul Anwar aged 12-16 years. This study was conducted in June-July. Inclusion Criteria Young women who are experiencing dysmenorrhea and do not use another aromatherapy. In this study, the average mean before given was 3.09 and the mean has been given to 2.00, based on the results of an independent t test in the p-value of 0.000 (p<0.05). In this study, it can be concluded that there is a significant influence of lemon aromatherapy menstrual pain on Grade 8 girls at Mts Mathla'ul Anwar.